Território da pesca: o uso do espaço aquático no Baixo Rio Solimões - Município de Manacapuru AM. - (:unkn) unknown (Universidade Federal do Amazonas, 2011)
The Amazon is abundant in natural resources. Its meadow and dry land environments are favorable to halieutical activities increasingly sought by ribeirinhos fishermen, people that live in the river banks of Amazon. Small-scale fishing is an activity commonly practiced by inhabitants of the Amazon region and this practice is not different in Costa do Laranjal, municipality of Manacapuru, State of Amazonas, the study field of this work. The fishing carried out by social actors from this area takes place in specific territorial locations, although these waterways are legally free access and open to the public. The management of these territories is held by local people, the social actors, inhabitants of that area. The purpose of this research is to analyze the use of the main river and the appropriation of the waterway, in base of the capital generated from water and their relations with the fishing industry. Necessary components for this work: A bibliographic survey, field research with semi-structured interviews and oral history reporting, the use of a GPS for fishing locations demarcation, camera and recorder, plus other methodological resources. In this way, the fishermen are subordinate to the processes created by capitalist production system itself. This relationship is of benefit to both; however entrepreneurs obtain the largest portion of total income. It was found that fishermen are subordinated to those processes imposed by capitalist economical system, developing its activities on land and water by combining them.
Keywords: Território; Territorialidade; Pesca; Comunidade; Territory; Territoriality; Fishing; Community; CIÊNCIAS HUMANAS: GEOGRAFIA